Impulse Noise Filtering Using Robust Pixel-Wise S-Estimate of Variance. (16th May 2010) - Crnojević Crnojević, Vladimir Vladimir; Petrović Petrović, Nemanja I. Nemanja I.
Abstract : A novel method for impulse noise suppression in images, based on the pixel-wise S-estimator, is introduced. The S-estimator is an alternative for the well-known robust estimate of variance MAD, which does not require a location estimate and hence is more appropriate for asymmetric distributions, frequently encountered in transient regions of the image. The proposed computationally efficient modification of a robust S-estimator of variance is successfully utilized in iterative scheme for impulse noise filtering. Another novelty is that the proposed iterative algorithm has automatic stopping criteria, also based on the pixel-wise S-estimator. Performances of the proposed filter are independent of the image content or noise concentration. The proposed filter outperforms all state-of-the-art filters included in a large comparison, both objectively (in terms of PSNR and MSSIM) and subjectively.